Strategi Efektif Untuk Pengembangan Bisnis UKM Yogyakarta Di Pasar Internasional: Studi Kasus UKM Wedang Uwuh Bu Yani - Yusuf Mustofa; Siti Nurfaizah; Agustin Eka Nurhayati; R. Sahedhy Noor SK (JURNAL MANAJEMEN, 2011)
This paper is the result of field research on SME business that is engaged in the drinks, especially the traditional drink in the wedang uwuh Imogiri area, Bantul. In this paper presented several business development strategies that can be carried out by SMEs wedang uwuh Mrs. Yani. Observed variables that includes strengths, weaknesses, opportunities, threats, and strategies for SME development wedang uwuh. Retrieval of datanusing this field metodewawancara, survey respondents are SMEs wedang uwuh Bu Imogiri Yani located in Bantul. The findings in the study include: In SMEs wedang uwuh Mrs. Yani, we found a lot of advantages, among others, a strategic location, as well as the many benefits of wedang uwuh good for health; drawback of these SMEs are at a less attractive product packaging, the composition of the packaging that is not the same between one another as well as products can not last longer than 6 weeks. Recommendation that we ask more, described in this paper.